Dark chaos - Dye, Ginny (Dye, Ginny. Bregdan chronicles series, 2015)
"Dark clouds and chaos descend lower upon America as the war rages around them -- threatening all they hold dear. Carrie & Robert are once more pulled apart, and Carrie finds herself the target of a hostile group of men determined to stop her from providing medical care to black residents of Richmond. How long can she continue to save other people's lives at the risk of her own? Riots erupt in the North, threatening those she loves, and she is pulled in to assist in a Richmond Prison escape. The ultimate test comes as the people of a once-promising nation must hold on to their faith and dreams as everything around them crumbles"--Author's website.